Pandangan Ḥanāfiyah dan Syāfi’iyah Tentang Kontradiksi Dalil Pemukulan Suami Terhadap Istri - Misbahul Huda; Fitria Maeliniatun Nazilah (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
There are source texts of Islamic law that allow and prohibit the beating of a husband against his wife. Thus it can be said that there is a contradiction in the argument for beating a husband against his wife. Meanwhile, there are different methods in resolving conflicts between arguments used by Ḥanāfiyah and Syafi'iyah scholars. This paper attempts to answer the views of Ḥanāfiyah and Syāfi'iyah regarding the law of beating a husband against his wife and how the methods of resolving conflicting arguments for beating a husband against his wife according to Ḥanāfiyah and Syāfi'iyah. This type of research is library research. The results of the study show that the Ḥanāfiyah and Syafi'iyah scholars both agreed to allow husbands to beat their wives who were nusyuz, it's just that there are some Syāfi'iyah who punish khilāf al-aulā. In resolving conflicting arguments, the majority of Ḥanāfiyah scholars use the nasakh method because the chronology of the text can be known clearly. While the majority of Syafi'iyah scholars use the al-jam'u wa al-taufiq method. According to Syafi'iyah practicing both propositions is better than completely ignoring one of them.